Kaji Eksperimen Pembakaran Tanah Gambut Pada Skala Laboratorium Dengan Laju Aliran Udara 3 M/Detik - Yogi Wibowo Agusta; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Peatlands play an important role in climate change and biodiversity which is currently increasingly threatened. Peat land in Indonesia is quite extensive, which is around 20.6 million ha or 10.8% of Indonesia's land area. In Sumatra, fires in wetlands / peat are a major problem that continues. At the same time, fire is used as a tool in the use of peat land, there is high population pressure and development on the land. It is necessary to identify, study and solve fire problems based on sustainable development and conservation of peatlands. This research method is to analyze the combustion triggering caused by cigarette butts and the rate of combustion that is affected by air flow. Peat testing is carried out on peat that has been dried in the oven for 8 hours. The sample treatment by giving cigarette butts as a trigger and giving air flow with the average speed of Riau province. The maximum temperature of peat combustion is 892 ° C and the average creepage velocity is 68.37 mm/hour. Burning cannot be triggered if the peat is wet.Keywords: peat fires, fire phenomena, influence of air flow